Musicians' Attitudes to Musical Influence - Nick Collins (Empirical Musicology Review, 2011)
This article discusses responses to an online survey on the topic of musical influence. 119 participants took part, answering both quantitative (five point Likert scale) and qualitative questions. A rich set of data was collected, which is summarized and analyzed in this paper. The primary research aim was to discover a good opinion base concerning issues of musical influence, to help illuminate some existing theories of influence, and in turn to inform further research directions. General trends observed included variation in attitudes to influences over time, the role of non- musical influences, and a usually positive attitude towards influences amongst participants.